PENGARUH KONEKSI POLITIK TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN: STABILITAS POLITIK SEBAGAI VARIABEL MODERASI - Sari Angriany Natonis (JAKA - Jurnal Jurusan Akuntasi, 2023)
This study aims to empirically examine the effect of political connections on corporate social responsibility disclosure, and the moderating effect of political stability on the influence between political connection and corporate social responsibility disclosure. Data used in this study comes from company sustainability reports, company annual reports, and the world bank website. The sample of this study consists of 190 high profile industry companies listed on the Indonesia Stock Exchange in the period 2019-2021. Corporate social responsibility disclosure is measured using CSRI based on the GRI 4 standard, the measurement of political connection using Political Exposed Persons in Bank Indonesia Regulations, while political stability is measured by the political stability index issued by World Governance Index. The analysis technique used in this study is Ordinary Least Square regression with the help of STATA 14. The results showed that (1) political connections had a significant positive effect on corporate social responsibility disclosure, (2) political stability does not moderate the effect of political connections on corporate social responsibility disclosure, but political stability has a significant positive effect directly on corporate social responsibility disclosure